Blunt thoracic aortic injury: A Western Trauma Association critical decisions algorithm. Issue 1 (24th January 2023) - Brown, Carlos V.R.; de Moya, Marc; Brasel, Karen J.; Hartwell, Jennifer L.; Inaba, Kenji; Ley, Eric J.; Moore, Ernest E.; Peck, Kimberly A.; Rizzo, Anne G.; Rosen, Nelson G.; Sperry, Jason L.; Weinberg, Jordan A.; et al.
Abstract : This is a recommended evaluation and management algorithm from the Western Trauma Association Algorithms Committee addressing the management of adult patients with Blunt Thoracic Aortic Injury.